Effects of RGD⁃grafted TiO2 nanotubes on the adhesion and proliferation of MG63 osteoblasts - DING Xian⁃ glong; WANG Jingxu; GUO Zehong; LAI Chunhua; GAO Yan; LIN Xi; XU Shulan (口腔疾病防治, 2018)
Objective To investigate the effect of pure titanium surface of large diameter TiO2 nanotubes modified by RGD peptide on the adhesion and proliferation of MG63 osteoblasts. to provide theoretical proof for developing titani⁃ um implants. Methods Commercially pure titanium discs were divided into four groups and treated with SLA to obtain a microrough surface (SLA group). Then, nanotubes were imposed on this microrough surface by anodization (SLA+ 80 group). The surface was then modified by dopamine (DOPA) (DOPA Group), after which bioactive RGD peptide layers were generated on the TiO2 nanotube surfaces via electrochemical and molecular self⁃assembly techniques (RGD group). The titanium surface morphology and elemental composition of each group were characterized by field emission scanning electron microscopy (FE⁃SEM) and X⁃ray photoelectron spectroscopy (XPS). MG63 cells were cultured in vitro to evalu⁃ ate biological activities of titanium before and after treatment, including the evaluation of early⁃stage cell adhesion capac⁃ ity by fluorescence microscopy, proliferation capacity by MTS assay, and mRNA expression of the cell osteoblast⁃related genes alkaline phosphatase (ALP) and osteocalcin (OCN) by qRT⁃PCR. Results FE⁃SEM and XPS showed that hierar⁃ chical micro/nanosurfaces decorated with TiO2 nanotubes were produced on titanium using sandblasting and large grit etching combined with anodization, dopamine was then self⁃polymerized to form a polydopamine film on the TiO2 nano⁃ tube surfaces, and RGD peptides were then conjugated to the polydopamine film, finally forming RGD peptide⁃modified bioactive layers. In vitro experiments showed that compared with the other three materials, the RGD⁃modified material was more conducive to cell adhesion and proliferation (P < 0.05). The expression levels of ALP and OCN mRNA in the RGD group were significantly higher than those in the SLA group and DOPA group (P < 0.05). Conclusion Hierarchi⁃ cal micro/nanosurfaces decorated with TiO2 nanotubes functionally modified with RGD peptides have good biocompatibil⁃ ity and could be used for developing titanium implants and further improving early osseointegration.